Advances in the enhanced removal of aqueous Hg(II) by metallic catalysts: a review. (September 2021) - Akmanova, Ainash; Nurlan, Nurbek; Han, Seunghee; Lee, Woojin
Graphical abstract: Highlights: Reductive removal of aqueous Hg(II) by metallic catalysts. Principal mechanisms of Hg(II) reduction by amalgamation and precipitation. High selectivity towards Hg(II) by metallic catalysts with surface functionalization. Superior durability and stability of metallic catalysts during repeated cycles. Future prospects of bimetallic catalysis of aqueous Hg(II). Abstract : Contamination of water sources by Hg(II) is still a severe environmental issue. Among various Hg(II) removal technologies, the metal-based reductive removal of Hg(II) has been considered as one of the promising and innovative approaches in natural and engineered aquatic environments. A critical review of the recent advances in the metallic catalysts was provided based on the summary of current existing environmental technologies. In this contribution, two types of Hg(II) reduction by metallic catalysts with supports and with surface functionalization (–SH and –NH) were summarized and discussed. This review also addressed the most critical operational parameters, durability of catalysts, and potential limitation in their applications for the treatment of water and wastewater. Finally, future prospects of catalytic Hg(II) removal technologies were provided.